Formation of entrepreneurial values through communication in entrepreneurial interactions in coastal areas - Subekti, Priyo; Bajari, Atwar; Sugiana, Dadang; Hafiar, Hanny (Manajemen Komunikasi, 2024)
This study examines how entrepreneurial values are fostered through interaction and communication between local and migrant entrepreneurs in coastal tourism areas. The study emphasizes the critical role of a shared understanding of these values, highlighting the need to promote local economic growth and develop a sustainable entrepreneurial ecosystem. Research objectives: This study aims to identify the factors that drive entrepreneurial values among local and migrant entrepreneurs in coastal tourism areas. Methods: A qualitative research approach was used, and data was collected through interviews and observations. The study focused on micro, small, and medium enterprises (MSMEs) operating in Pangandaran. The research shows that essential attributes of business success - such as grit, new ideas, and a willingness to stand on one’s own two feet - come from life experiences and the give-and-take within the community and culture. Both local entrepreneurs and travelers can use social connections and circles as tools for growth and support. At the heart of this discovery? These sociable traits are passed down through different groups, while language skills are spread across many places. Together, they create resilient people skilled in business and entrepreneurship. This Recommendation focuses on increasing collaboration between entrepreneurs through mentoring programs, workshops, and networking events to encourage the exchange of knowledge and experience. These initiatives are expected to increase innovation, competitiveness, and business sustainability in coastal tourism, strengthening the entrepreneurial ecosystem.